MAKING WEBSITE-BASED ADVERTISING MEDIA USING WORDPRESS CMS FOR MSME EKMIRA ALMOND CRISPY MALANG - Bachtiar, Mochammad Yusuf; Maskur, Maskur (Transpublika Publisher, 2024)
Ekmira Almond Crispy Malang is an MSME engaged in pastries. In marketing activities so far they use social media such as Instagram, Tiktok, Whatsapp. However, the information conveyed through their website is not optimal because of the lack of detailed information regarding Ekmira Almond Crispy products. The audience who follows the content on social media are not engaged. So people do not know about Ekmira Almond Crispy Malang. This research is intended to make a website as an advertising medium using CMS Wordpress. The type of research conducted in this study was action research. Data testing was done by distributing questionnaires based on the criteria for measuring the effectiveness of WebQual design (usability, information quality, interaction quality) to 1 owner, 2 marketing experts, 2 computer experts. The answer choices used a Likert scale with a range (1 for strongly disagree to 5 for strongly agree). The data processing method used simple tabulation analysis and average scores. In this study, the results of WebQual score in the first cycle of usability indicator section get a value of 85% with an average of 4.27 out of 5.0. In the information quality indicator it gets a value of 75% with an average of 3.73 out of 5.0. In the interaction quality indicator the score is 79% with an average of 3.93 out of 5.0. Based on this research it can be concluded that the Ekmira Almond Crispy website can be published in terms of WebQual testing.